Bolivia en el contexto de la crisis económica internacional - Javier Aliaga Lordemann; Tirza J. Aguilar; Sergio Téllez von Borries (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2009)
– The current research has the aim to identify and evaluate the impacts of external shocks related to the new economic context of world-wide deceleration in the Bolivian economy. It is assumed for this scenario that Bolivia would face a reduction in the export prices, a reduction in the level of foreign direct investment, a fall in the remittances and a decline in the government expenditure. In order to evaluate these effects in the short and medium term, we use a dynamic General Equilibrium Computable Model (CGE), in a horizon of ten years. The exercise was realized on the basis of the following experiments: i) an adverse shock in terms of trade, ii) a negative shock in the level of government spending, iii) a negative shock in the level of remittances and direct foreign investment (DFI)
Keywords: 330